Scenario Analysis of Indonesian Ferronickel Supply Chain Resilience with System Dynamics - Tul Munikhah, I Anna; Ramdhani, Ade Yanyan; Pratama, Aiza Yudha; Arini, Ratih Windu (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study aims to determine the impact of Indonesian government policies on the supply chain resilience of the ferronickel industry in Indonesia. The existing problem is that the law prohibits nickel ore exports, and the policy of industrial downstream causes delays in the process of nickel processing. The problems happen because Indonesia's nickel industry is still incapable of downstream. As a result, the nickel supply chain faces dynamic and complex events that can disrupt operational activities. At the same time, supply chains need to withstand and recover from disruptions quickly. Therefore, Supply Chain Resilience, which is the ability to survive, adapt, and recover from disruptions to meet customer needs, is needed. This study uses system dynamics to analyze complex and dynamic systems to provide more practical policy advice. The system dynamics model starts by building a conceptual model through a system diagram. Inside the model is a causal loop diagram, then proceeds with developing a quantitative stock flow diagram (SFD) model. Finally, this SFD model operated with several scenarios used as policy suggestions for the Indonesian government.